Safe Newborn Sleep Practices on a Large Volume Maternity Service. Issue 1 (January 2023) - Stone, Gabrielle; Chase, Allison; Vidrine, Dana C.; Singleton, Wendy W.; Kitto, Laurel; Laborde, Kelly; Harper, Jeannie; Sutton, Elizabeth F.
Abstract: Purpose: Reinforcing safe infant sleep conditions in the hospital setting supports continuation of safe sleep practices after hospital discharge and should be considered the first line of defense for reducing risk for sudden unexpected infant death (SUID) and sudden infant death syndrome (SIDS) at home. The purpose of this study is to determine knowledge of perinatal nurses, nursing assistants, physicians, and ancillary personnel about safe sleep recommendations and implementation of safe sleep practices on the mother–baby unit. Study Design and Methods: Nurses and other members of the perinatal health care team in a level III maternity service were invited to participate in a survey about safe sleep knowledge and practices. An audit for safe sleep adherence was conducted on the mother–baby unit for 120 mother–baby couplets over 1 year as a process improvement project. Results: N = 144 surveys were completed; most participants (86%) were nurses. They had high levels of knowledge about safe sleep recommendations and 74% reported making at least one safe sleep adjustment during one shift per week. The most common modifications at least once per week were removing baby from a sleeping caregiver (30%) and removing items from baby's bassinet (26%). Safe sleep audit findings revealed 32 out of 120 couplets were not fully following safe sleep recommendations, with most common unsafe sleep practice metrics being items in the baby's bassinet (18%) and bassinets propped up (8%). Clinical Implications: During the hospitalization for childbirth, new parents can learn about safe sleep practices from the perinatal health care team. Sharing information and role modeling safe sleep practices can promote continuation of safe sleep practices for the newborn at home after hospital discharge. Abstract : Nurses and other members of the maternity care team have the opportunity to teach new parents about safe newborn sleep recommendations and role model safe sleep practices during postpartum hospitalization to promote safe sleep for the newborn at home after hospital discharge.